Effects of Feedstock and Pyrolysis Temperature on Biochar Adsorption of Ammonium and Nitrate - Gai, Xiapu; Wang, Hongyuan; Liu, Jian; Zhai, Limei; Liu, Shen; Ren, Tianzhi; Liu, Hongbin (PLOS ONE, 2014)
Biochar produced by pyrolysis of biomass can be used to counter nitrogen (N) pollution. The present study investigated the effects of feedstock and temperature on characteristics of biochars and their adsorption ability for ammonium N (NH4+-N) and nitrate N (NO3−-N). Twelve biochars were produced from wheat-straw (W-BC), corn-straw (C-BC) and peanut-shell (P-BC) at pyrolysis temperatures of 400, 500, 600 and 700°C. Biochar physical and chemical properties were determined and the biochars were used for N sorption experiments. The results showed that biochar yield and contents of N, hydrogen and oxygen decreased as pyrolysis temperature increased from 400°C to 700°C, whereas contents of ash, pH and carbon increased with greater pyrolysis temperature. All biochars could sorb substantial amounts of NH4+-N, and the sorption characteristics were well fitted to the Freundlich isotherm model. The ability of biochars to adsorb NH4+-N followed: C-BC>P-BC>W-BC, and the adsorption amount decreased with higher pyrolysis temperature. The ability of C-BC to sorb NH4+-N was the highest because it had the largest cation exchange capacity (CEC) among all biochars (e.g., C-BC400 with a CEC of 38.3 cmol kg−1 adsorbed 2.3 mg NH4+-N g−1 in solutions with 50 mg NH4+ L−1). Compared with NH4+-N, none of NO3−-N was adsorbed to biochars at different NO3− concentrations. Instead, some NO3−-N was even released from the biochar materials. We conclude that biochars can be used under conditions where NH4+-N (or NH3) pollution is a concern, but further research is needed in terms of applying biochars to reduce NO3−-N pollution.